MOLECULAR DOCKING STUDIES OF TETRAZOLE DERIVATIVES ON COX-2 PROTEIN RESIDUE - R. ARULMOZHI; HELEN P. KAVITHA; N.ABIRAMI; R.ARUL MURUGAN (International Journal of Pharma and Bio Sciences, 2015)
Tetrazoles are the hetrocyclic compounds having diverse biological activities such as analgesic, anti-inflammation, antimicrobial, anticancer, antidiabetic etc., and an impending source in biosciences. Invivo analysis was carried out on anti-inflammatory property of synthesized five tetrazole derivatives (a, b, c, e and g) which revealed that the compound(g) exhibited potential anti-inflammatory activity of 49% when compared to standard Indomethacine at10µg/ml in the previous report by the authors.In the present investigation, molecular docking studies were performed for the above tetrazole derivatives to evaluate the in- silico anti-inflammatory activity against Cycloxigenase-2 (COX-2) protein as model compound and the data was compared with Indomethacine